2013
DOI: 10.1517/17460441.2013.769520
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the design of ITK inhibitors

Abstract: The majority of currently available ITK inhibitors either lack comprehensive selectivity data or evidence of their ability to effectively suppress T-cell signaling in cells or animal models. Although inhibitors targeting an inactive conformation of ITK have yielded the predicted phenotype, it remains unclear to what extent the observed biological activity is due to inhibition of the kinase activity of ITK. With available biological data suggesting the possibility of functional redundancy of ITK, the suitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…We are currently investigating rational treatment combinations between ITK inhibitors and standard treatments for metastatic melanoma in various preclinical melanoma models that may serve as the basis for future clinical trials in metastatic melanoma. Besides BI 10N, several other ITK inhibitors previously have been developed to target Th2 dominant autoimmune, inflammatory, and infectious diseases (48, 49). Notably, ibrutinib (IMBRUVICA, Pharmacyclics, Inc.), an irreversible inhibitor of BTK and ITK (50), has been granted approval by the U.S. Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently investigating rational treatment combinations between ITK inhibitors and standard treatments for metastatic melanoma in various preclinical melanoma models that may serve as the basis for future clinical trials in metastatic melanoma. Besides BI 10N, several other ITK inhibitors previously have been developed to target Th2 dominant autoimmune, inflammatory, and infectious diseases (48, 49). Notably, ibrutinib (IMBRUVICA, Pharmacyclics, Inc.), an irreversible inhibitor of BTK and ITK (50), has been granted approval by the U.S. Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not perform a head-to-head comparison of both inhibitors, evaluations of the potency of such ITK targeting have to consider the effects of individual drug selectivities (5). The affinity of PRN694 to ITK is reported to be higher than for BMS-509744 (IC 50 values: 0.3 nM versus 15 nM) (5).…”
mentioning
confidence: 99%
“…TEC kinases are dysregulated in several malignancies, including chronic lymphocytic leukemia (CLL), mantle cell lymphoma (MCL), multiple myeloma and diffuse large B-cell lymphoma (DLBCL) [81][82][83].…”
Section: Tec Protein Kinasementioning
confidence: 99%
“…BMS-509744 is a selective ATP-competitive inhibitor of ITK with an IC 50 value of 19 nM (Table 1) [83]. The inhibitory effects of this TKI have not been well studied in malignancies; however, several studies have shown the inhibitory effects in inflammatory and infectious diseases [96,97].…”
Section: Bms-509744mentioning
confidence: 99%